Women on high-level boards of banks and insurance companies: Growth coming to a standstill on supervisory boards - Elke Holst; Katharina Wrohlich (DIW Weekly Report, 2019)
The proportion of women on executive boards of the 100 largest banks stagnated at almost nine percent in 2018. In the 60 largest insurance companies, the proportion increased by a good percentage point to almost ten percent. While growth on executive boards has been weakening in past years, it is now slowing down on supervisory boards in the financial sector as well. In 2018, the proportion of women on financial sector supervisory boards remained at around 23 percent. If the current linear development were to continue, it would now take longer-almost until the beginning of the next century- for the top bodies to be composed of equal numbers of men and women. Compared to men, women in the financial sector are less likely to be promoted to senior management positions than in any other sector. This is due to, among other things, particularly inflexible working structures for managers, which ensure that women are hardly represented in middle management although they make up the majority of employees.
Keywords: G2; J16; J78; L32; M14; M51; 330; board composition; board diversity; boards of directors; central banks; corporate boards; Europe; finance industry; financial sector; female directors; Gender gap; gender equality; gender quota; Germany; insurance companies; management; public and private banks; supervisory boards; women CEOs